Pembaharuan Hukum Islam: Perspektif Muhammad Abduh - Moh Munir (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
This study aims to analyze the concept of Islamic law reform in the perspective of Muhammad Abduh and its relevance in the context of modern Islamic law. The method used is normative juridical research with a historical and conceptual approach, through a study of the literature of Abduh's works and the thoughts of contemporary scholars. The results of the study show that Abduh emphasizes ijtihad as the main instrument in the renewal of Islamic law, by rejecting taqlid which limits the development of law. He argues that Islamic law must be dynamic and able to adapt to social change, without neglecting the basic principles of sharia. His thinking made a significant contribution to the reform of Islamic law, especially in building a legal system that is more rational and in line with the needs of modern society. This study emphasizes the importance of a contextual approach in understanding and developing Islamic law.